Совершенствование кадровой политики образовательных учреждений - Koltasheva Y. D. (Educational environment today: development strategy, 2016)
To carry out the selection and training of future teachers a program is needed that involves the establishment of systematic work. The concept of improving education in the Russian Federation is aimed at increasing the professional level of teachers, the formation of the teaching cluster that is necessary to improve the educational system in the Russian Federation.
Keywords: система образования; кадровая политика; управление персоналом; педагогические кадры; стратегия; personnel management; strategy; formation; system of education; формирование кадрового состава; приоритеты развития образования; personnel policy; priorities of educational development; pedagogical personnel